2003
DOI: 10.1021/jo0267100
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Desaturation of Fatty Acids:  Δ11 Desaturase Activity on Cyclopropane Acid Probes

Abstract: The formation of methylenecyclopropanes by enzymatic desaturation of 11-cyclopropylundecanoic acid (1) and its disubstituted derivatives cis- and trans-3-5 has been investigated using the Delta(11) desaturase of Spodoptera littoralis as model enzyme. Gas chromatography coupled to mass spectrometry analyses of methanolyzed lipidic extracts from tissues incubated with each probe revealed that all the cyclopropyl fatty acids were transformed into the corresponding 11-cyclopropylidene acids, except for compound tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…A recent computational study has concluded that P-450-catalyzed desaturations proceed via a cationic intermediate and are favored by steric hindrance to recombination of the initial carbon radical and iron-bound oxygen (45). Interestingly, a previous attempt to demonstrate the involvement of a radical intermediate in a non-P-450 desaturation reaction by placing a cyclopropyl ring on the carbon that is oxidized was unsuccessful, presumably because the cyclopropyl ring opening was too slow in that system to compete with the desaturation process (46).…”
Section: Fig 4 Gc Traces For the Reactions Of P-450 Cam And P-450 Bm3mentioning
confidence: 99%
“…A recent computational study has concluded that P-450-catalyzed desaturations proceed via a cationic intermediate and are favored by steric hindrance to recombination of the initial carbon radical and iron-bound oxygen (45). Interestingly, a previous attempt to demonstrate the involvement of a radical intermediate in a non-P-450 desaturation reaction by placing a cyclopropyl ring on the carbon that is oxidized was unsuccessful, presumably because the cyclopropyl ring opening was too slow in that system to compete with the desaturation process (46).…”
Section: Fig 4 Gc Traces For the Reactions Of P-450 Cam And P-450 Bm3mentioning
confidence: 99%
“…These pheromone components are synthesized de novo in the pheromone gland, from acetyl-CoA [involving acetyl-CoA carboxylase (ACCase) and fatty acid synthetase] to fatty acids as a response to the neurohormonal signal transmitted by PBAN (Jurenka, 2003;Rafaeli and Jurenka, 2003). The production of fatty acid analogs is followed with the double bond positioning as a result of the action of unique desaturases to make mono-and di-unsaturated fatty acids (Tang et al, 1989;Roelofs, 1981, 1983;Rosell et al, 1992;Jurenka et al, 1994Jurenka et al, , 2003Foster and Greenwood, 1997;Jurenka, 1997;Wu et al, 1998;Svatos et al, 1999;Abad et al, 2001;Choi et al, 2002;Ono et al, 2002;Rodriguez et al, 2002;Villorbina et al, 2003). The involvement of desaturases in the production of sex pheromones is known to be a derived function found only in insects thus far (Roelofs and Rooney, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…1 double bond in Z9,E12-14:Ac from Z9-14:Acid; and/or a D14 desaturase producing the second double bond in Z9,E12-14:Ac from Z11-16:Acid. Biosynthetic pathways have been studied in a number of moth species utilizing labeled precursor fatty acids in combination with the identification of possible fatty acid intermediates (Tang et al, 1989;Roelofs, 1981, 1983;Rosell et al, 1992;Jurenka et al, 1994Jurenka et al, , 2003Foster and Greenwood, 1997;Jurenka, 1997;Wu et al, 1998;Svatos et al, 1999;Abad et al, 2001;Choi et al, 2002;Ono et al, 2002;Rodriguez et al, 2002;Villorbina et al, 2003). Demonstrations of the rate-limiting enzyme primarily rely on experiments in which labeled precursors and intermediates are tracked into the pheromone component/s in the absence and presence of PBAN.…”
Section: Introductionmentioning
confidence: 99%
“…Progeldanamycin therefore is very likely to have a C-4,5 saturated ansamycin system, which leads to the intriguing question of how the cis double bond is introduced. Catalysis by a fortuitous desaturase, utilizing a mechanism similar to that involved in the oxidative desaturation of fatty acids (34), is one possibility. However, this type of biochemical mechanism has not been reported for the biosynthesis of polyketide secondary metabolites to our knowledge.…”
Section: Discussionmentioning
confidence: 99%